A novel bioassay for thyroid-blocking immunoglobulins - George, Augustine; Lotz, Johannes; Luffy, Maximilian; Ganz, Anna-Lena; Wolf, Jan; Kahaly, George J. (Frontiers in Endocrinology, 2024)
Background: Thyroid-blocking immunoglobulins (TBI) are present in 10-15% of patients with autoimmune thyroid disease (AITD). TBI affect thyroid function. The analytical performance of a novel TBI bioassay was evaluated. Methods: Sera from AITD patients were tested with a cell-based TBI reporter bioassay (Thyretain®) with expression of a Luciferase transgene as readout and a new “TurboTM” TBI bioassay with a readout based on a cyclic AMP-activated luciferase. All samples were also run on two TSH-R binding immunoassays. A Passing-Bablok regression, a Bland Altman plot, and user/lot comparisons were performed. In addition, dose-response curves for Turbo and Thyretain were fitted using serial dilutions and half maximal and 80% inhibitory concentrations (IC50 /IC80) were compared. Results: Of 1011 unselected AITD patients, 131 patients (212 samples) were TBI positive. Of 212 samples, 149 (70.3%), 47 (22%) and 16 (7.5%) were hypothyroid, euthyroid and hyperthyroid, respectively. The three thyrotropin receptor antibody (TSH-R-Ab) assays were negative in 90 controls devoid of autoimmune thyroid disorders. In contrast, the Turbo cyclic adenosine 3’,5’-monophosphate (cAMP) TBI, Thyretain TBI and the binding assays detected TBI in 212 (100%), 168 (79%) and 138/180 (65%) samples, respectively (p<0.001). Turbo highly correlated with thyroid function (p<0.001). The percentage inhibition in both Turbo and Thyretain correlated with TSH-R-Ab binding assay positivity (both p<0.001). The two bioassays correlated (r =0.8, p<0.001) and the Bland-Altman plot displayed no significant bias (0.24). Values scatter with slight systemic deviation between TBI mean values of 10–50% inhibition with higher Turbo than Thyretain results. Intra-assay validation demonstrated adequate precision with very low coefficient of variation (average CV 5.4%) and lower CV with samples with high inhibitory effect (CVAverage= 1.7% for a sample with 95% inhibition Thyretain). CV did not differ between users (p=0.35) and lots (p=0.121). IC50/IC80 values were 1.55 ng/ml/3.48ng/ml for Turbo and 6.76 ng/ml/18.46 ng/ml for Thyretain, respectively demonstrating the markedly higher sensitivity of Turbo. Conclusions: The novel, easy-to-perform, rapid and reliable Turbo TSH-R blocking bioassay detected significantly more TBI than the established immunoassays emphasizing its higher analytical performance and clinical utility in the management of patients with AITD.